Effects of Adhesive Agent on Shear Stiffness of Fabrics Bonded with Adhesive Interlining (Journal of Fiber Bioengineering and Informatics, 2012)
The effects of adhesive agent on shear stiffness of laminated fabrics bonded with adhesive interlining wereinvestigated. The shear stiffness of face fabrics made of different weave density and adhesive interliningsmade of different adhesive condition for mass, number and diameter were measured. As adhesiveagent mass increases, shear stiffness values of adhesive interlining and laminated fabric is increased.Furthermore, as weave density of face fabric increases, shear stiffness of face fabrics is increased. Theincreasing rate (I.R.) of shear stiffness for face fabric by bonding adhesive interlining was obtainedfrom the difference between shear stiffness of laminated fabric and pressed adhesive interlining. Therelationship between fixed crossing points of warp and weft by adhesive agents per all crossing points ofwarp and weft (F.C. (%)), and adhesive agent mass and number was investigated. A prediction methodwas proposed using the increasing rate (I.R.) and F.C. (%). The predicted shear stiffness of laminatedfabric showed good agreements with experimental ones.
Keywords: Shear Stiffness; Torque; Crossing Point; Adhesive Agent Mass; Laminated Fabric; Adhesive Interlining